The Influence of Audiovisual Media on Improving Adolescents' Knowledge of Reproductive Health - Erika Yulita Ichwan; Willa Follona; Sri Sukamti (Journal of Midwifery, 2021)
Various adolescent health problems in Indonesia are so complex, not only related to physical but also related to psychosocial aspects. When teenagers have to struggle to recognize the sides of themselves that are experiencing physical-psychic and social changes due to puberty, society instead tries to hide everything about sex and leave teenagers with question marks in their minds. The view that sex is taboo, makes teenagers reluctant to discuss reproductive health with others. The lack of accurate and correct information about reproductive health makes teenagers seek access and explore themselves. Health education for adolescents needs to be provided with the right methods and media. Audiovisual media is a learning tool or media that uses video or mobile display, this media is a modern learning among the community and effective for teenagers so that they can absorb the material provided to the maximum.This study aims to determine the influence of audiovisual media on increasing adolescent knowledge about reproductive health. This research is a quantitative study with quasi-experimental design one group without control, with a sample of 50 respondents. Respondents measured the rate ofyears before and after intervention, namely health education using audiovisual media.The results of the study: dependent t-test dependent statistical test on post-test knowledge about reproductive health increased by 6.46 to 8.06 with p value of 0.000 indicating the influence of audiovisual media provision on improving adolescent reproductive health knowledge.